2020 IFPRI audited financial statements - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
In our opinion, the financial statements referred to above present fairly, in all material respects, the financial position of IFPRI as of December 31, 2020 and 2019, and the changes in its net assets and its cash flows for the years ended in accordance with accounting principles generally accepted in the United States of America.